Building National Capacity in the Health, Nutrition and Population Sector : A Perspective - Vaillancourt, Denise (World Bank, Washington, DC, 2012)
The note reflects on the issue of effective health sector investments with sustainable results, which based on the Bank's experience, constraints to such efforts is neither lack of money, nor absence of technology, but rather the weak national capacity to fully benefit from those investments. This has been documented, noting that while the Bank's Population, Health and Nutrition (PHN) portfolio assessed positive evolutions in quantity, and quality of these PHN projects, also highlighted was the issue of serious weaknesses by the Bank, in the assessment of national capacity to implement these projects, including in the design and implementation of institutional strengthening, needed to support investments in the sector. Unfortunately this weakness persists, as documented by the recent Operations Evaluation Department review of development effectiveness. These observations fostered the development of a new framework for institutional assessment, and design of interventions for capacity building, whose application has shown promising results. The note provides experiences from Niger and Burkina Faso, which entail paradigm shifts both for the Bank, as well as for governments, but, while the experience thus far seems encouraging, serious challenges remain. The Bank should ensure support to ongoing reforms for decentralization, and integration, through the choice of appropriate performance indicators for which local actors will be held accountable, and continue its evolution in the context of innovations, and policies, focused on cost-effectiveness, and financial requirements.